2014
DOI: 10.1037/2332-2136.1.s.58
|View full text |Cite
|
Sign up to set email alerts
|

The effect of five smoking cessation pharmacotherapies on smoking cessation milestones.

Abstract: Objective-Most smoking cessation studies use long-term abstinence as their primary outcome measure. Recent research suggests that long-term abstinence may be an insensitive index of important smoking cessation mechanisms. The goal of the current study is to examine the effects of five smoking cessation pharmacotherapies using Shiffman et al. 's (2006) approach of examining the effect of smoking cessation medications on three process markers of cessation or smoking cessation "milestones": initial abstinence, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…It has been observed that pharmacotherapy has a limited effect on preventing patients from resuming smoking. Treatment with NRTs has been shown to more effectively aid initial abstinence compared to bupropion [23]. In studies that have attempted to prevent relapse by prolonging varenicline and bupropion treatment, only varenicline showed a preventative effect [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that pharmacotherapy has a limited effect on preventing patients from resuming smoking. Treatment with NRTs has been shown to more effectively aid initial abstinence compared to bupropion [23]. In studies that have attempted to prevent relapse by prolonging varenicline and bupropion treatment, only varenicline showed a preventative effect [24].…”
Section: Discussionmentioning
confidence: 99%
“…Así, el reforzamiento positivo refleja los efectos inherentemente gratificantes y agradables que aumentan la probabilidad de autoadministración. Sin embargo, en el año 1974, Rusell reportó el reforzamiento negativo como un efecto de la nicotina para aliviar el estado afectivo desagradable inducido por los déficits cognitivos y otros síntomas negativos asociados con la abstinencia a esta sustancia (41).…”
Section: Contextualización Del Consumo a La Adicciónunclassified
“…75 In treatment evaluation research, a series of survival analyses can be used to test whether treatment condition influences the time to each milestone, providing clues as to how effective treatments work. 75,76 An assumption here is that these milestones are differentially sensitive to medication effects and their relations with omic determinants. For instance, there is some evidence that the effects of medication early in the quit attempt (e.g., on initial abstinence) are especially sensitive to medication benefit.…”
Section: Phenotype Assessmentmentioning
confidence: 99%